The Tension of Religious-Traditions and the Ideas of Women's Liberation in Dreams of Trespass’ Novel by Fatima Mernisi - Asmarani, Dini; Monica, Sarah; D. Ratri, Sari (Jurnal Lektur Keagamaan, 2022)
ABSTRACT This article aims to analyze the literary work entitled "Dreams of Trespass: Tales of a Harem Girlhood," which reflected Fatima Mernissi's critical viewpoint in the struggle for gender equality. Utilizing a literature review and textual analysis, this study attends to how Mernissi told a story of women's liberation discourses in her literary work. Mernissi's work cannot be seen as entirely fictional, as it incorporated Mernissi's own experiences in growing up within a harem-living family. The findings reveal that Mernissi’s work is a reflection on reality, as well as, an aspiration for the ideal future in which women and men would have equal responsibilities and rights. This article concludes that Mernissi's critical feminism must be placed in the context of the life in which the work was written and the historical time it tells, namely, the 20th century of Arabic culture and Islamic religiosities in Morocco. At that time, the world had transitioned from the colonization period to the rise of global nationalism in conquered nations, including Morocco. This transition resulted in the clash of religion-tradition and modernity that affects women's thinking and perceptions about gender equality based on universal humanism principles and Qur'anic religious interpretations. Therefore, this article provides an alternative outlook in viewing literary work as a representation of the experiences and developments of thought of Fatima Mernissi.  Keywords: Fatima Mernissi, Gender equality, Literary work, Muslim feminist, Textual analysis.   ABSTRAK Tujuan penulisan artikel ini adalah untuk mengkaji novel berjudul “Perempuan-perempuan Haremku” sebagai sebuah karya sastra yang menampilkan pemikiran kritis Fatima Mernissi dalam memperjuangkan kesetaraan gender. Artikel ini menggunakan metode kajian literatur dengan analisis teks untuk melihat bagaimana Mernissi menarasikan wacana pembebasan perempuan melalui karya sastra yang tidak sepenuhnya bersifat fiksi. Hasil temuan kami menunjukkan bahwa karya Mernissi juga berangkat dari pengalaman sang penulis yang berasal dan besar dari kehidupan keluarga di dalam harem. Karya tersebut merupakan sebuah refleksi atas realitas, sekaligus aspirasi masa depan yang ideal untuk kesetaraan peran dan hak antara perempuan dan laki-laki. Para penulis artikel ini berkesimpulan, pemikiran kritis feminisme Mernissi harus ditempatkan pada konteks kehidupan di mana karya tersebut ditulis dan waktu sejarah yang dikisahkan di dalamnya, yakni terkait dengan kultur Arab dan keberagamaan Islam di Maroko pada abad 20. Dalam konteks periode tersebut, dunia sedang mengalami peralihan dari masa kolonialisme ke gerakan nasionalisme global di negara-negara terjajah termasuk Maroko. Sehingga ada perbenturan tradisi dan modernitas yang mewarnai gagasan-gagasan perempuan dan tentang perempuan terkait kesetaraan gender berdasarkan nilai humanisme universal serta tafsir keagamaan dalam kitab suci Islam. Dengan demikian, artikel ini menawarkan pemikiran alternatif dalam melihat karya sastra sebagai representasi pengalaman dan perkembangan pemikiran seorang tokoh Fatima Mernissi. Kata kunci: Analisis Teks, Fatima Mernissi, Feminis Muslim, Karya Sastra, Kesetaraan Gender.